Differences in symptom clusters before and twelve months after breast cancer surgery. (February 2018) - Mazor, Melissa; Cataldo, Janine K.; Lee, Kathryn; Dhruva, Anand; Cooper, Bruce; Paul, Steven M.; Topp, Kimberly; Smoot, Betty J.; Dunn, Laura B.; Levine, Jon D.; Conley, Yvette P.; Miaskowski, Christine
Abstract: Purpose: Given the inter-relatedness among symptoms, research efforts are focused on an evaluation of symptom clusters. The purposes of this study were to evaluate for differences in the number and types of menopausal-related symptom clusters assessed prior to and at 12-months after surgery using ratings of occurrence and severity and to evaluate for changes in these symptom clusters over time. Methods: Prior to and at 12 months after surgery, 392 women with breast cancer completed the Menopausal Symptoms Scale. Exploratory factor analyses were used to identify the symptom clusters. Results: Of the 392 women evaluated, the mean number of symptoms (out of 46) was 13.2 (±8.5) at enrollment and 10.9 (±8.2) at 12 months after surgery. Using occurrence and severity, three symptom clusters were identified prior to surgery. Five symptom clusters were identified at 12 months following surgery. Two symptom clusters (i.e., pain/discomfort and hormonal) were relatively stable across both dimensions and time points. Two symptom clusters were relatively stable across both dimensions either prior to surgery (i.e., sleep/psychological/cognitive) or at 12 months after surgery (i.e., sleep). The other four clusters (i.e., irritability, psychological/cognitive, cognitive, psychological) were identified at one time point using a single dimension. Conclusions: While some menopausal-related symptom clusters were consistent across time and dimensions, the majority of symptoms clustered together differently depending on whether they were evaluated prior to or at 12 months after breast cancer surgery. An increased understanding of how symptom clusters change over time may assist clinicians to focus their symptom assessments and management strategies. Highlights: Prior to and at 12 months after surgery, patients reported an average of 11 symptoms. Hormonal and pain/discomfort symptom clusters were identified regardless of time and dimension. Clusters that included psychological, cognitive and sleep symptoms varied over time. Identification of symptom clusters can guide symptom management interventions.